Histomorphological Studies of the Organs of Malaria Mice Model After Administration Combination of Leaf and Stem Bark Extract of Syzygium cumini with Chloroquine - Lilik Maslachah1 , Lucia Tri Suwanti2 , Hardany Primarizky3 ,Thomas V Widiyatno4 , Dyah Fitria Ratna (Indian Journal of Forensic Medicine & Toxicology, 2020)
This study aims to assess the histomorphological finding of the in spleen, brain, kidneys and lungs organin malaria mice model after administration combination of Leaf and Stem bark extract of Syzygiumcumini with chloroquine. Thirty-five male albino mice were randomly assigned into 7 treatment groups.K0: not infected, K1: infected. K2: infected+chloroquine. P1: infected+Syzygium cumini leaf extract. P2: infected+chloroquine+Syzygium cumini leaf extract. P3: infected +Syzygium cumini stem bark extract.P4: infected +chloroquine+ Syzygium cumini stem bark extract. Therapy was given once a day for 4 daysafter 24 hours post infection. The 21stday, mice were euthanasia. The organs were taken in order to makehistopathology preparations, stained with hematoxylin and eosin. The combination of Syzygium cumini leafextract and chloroquine in mice infected with P. berghei can reduce cerebrum and cerebellum microglia cellcounts, white pulp diameter size, haemorrhages damage, alveolar congestion, edema and thickened alveolarsepta of lung, decreased tubular necrosis, and interstitial nephritis of renal.